Gestión administrativa y su incidencia en los procesos de contratación pública del hospital general Quevedo año 2023. - Yanqui Yépez, Nataly Juliana (2025)
Administrative management plays a fundamental role in the efficiency and transparency of public procurement processes in the health sector. This research aims to evaluate the incidence of administrative management in the public contracting processes of the Quevedo General Hospital in the year 2023. A qualitative-quantitative approach was used through the use of interviews and surveys. To identify limitations of the administrative management in the contracting processes through the small amount procedure and reverse auction, an efficiency of 80% was obtained, considered good, in the same way, compliance with the Organic Law of the National Public Contracting System in the public contracting processes was analyzed, obtaining an efficiency of 85% established as very good, on the other hand, the efficiency and transparency of the public contracting processes was evaluated to improve administrative management, obtaining an efficiency of 80%. There is a direct impact between administrative management and public procurement processes, but obstacles are evident that must be improved; the respondents' opinions are in the affirmative part of the indicators.